2020
DOI: 10.3847/1538-4357/ab7ead
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Inner Regions of Protoplanetary Disks

Abstract: We present a study of the evolution of the inner few au of protoplanetary disks around low-mass stars. We consider nearby stellar groups with ages spanning from 1 to 11 Myr, distributed into four age bins. Combining PANSTARSS photometry with spectral types we derive the reddening consistently for each star, which we use (1) to measure the excess emission above the photosphere with a new indicator of IR excess and (2) to estimate the mass accretion rate (Ṁ ) from the equivalent width of the Hα line. Using the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 142 publications
(232 reference statements)
2
12
0
1
Order By: Relevance
“…Still, the level of photoevaporative mass loss rate is unclear. For example, Manzo-Martínez et al (2020) found that the mass loss rate of ∼ 1 − 3 × 10 −9 M yr −1 is consistent with the observed disk fraction in a wide age range. Nevertheless, mass accretion rates much lower than these limits are still observed in many sources (Thanathibodee et al 2018(Thanathibodee et al , 2020Manara et al 2016;Hartmann et al 2016).…”
supporting
confidence: 68%

A Census of the Low Accretors. I: The Catalog

Thanathibodee,
Calvet,
Hernandez
et al. 2022
Preprint
Self Cite
“…Still, the level of photoevaporative mass loss rate is unclear. For example, Manzo-Martínez et al (2020) found that the mass loss rate of ∼ 1 − 3 × 10 −9 M yr −1 is consistent with the observed disk fraction in a wide age range. Nevertheless, mass accretion rates much lower than these limits are still observed in many sources (Thanathibodee et al 2018(Thanathibodee et al , 2020Manara et al 2016;Hartmann et al 2016).…”
supporting
confidence: 68%

A Census of the Low Accretors. I: The Catalog

Thanathibodee,
Calvet,
Hernandez
et al. 2022
Preprint
Self Cite
“…For low-mass stars, this fraction is 5% (e.g. Damjanov et al 2007;Bayo et al 2012;Riaz et al 2012;Dawson et al 2013;Downes et al 2015;Manzo-Martínez et al 2020). These results suggest that VLMSs and BDs could retain their primordial disks for longer times than more massive stars; the times may be up to several tens of million years.…”
Section: Disk Modelmentioning
confidence: 90%
“…For instance, at ages of " 7Myr, " 30% of the BD still retain their disks in contrast with the 5% for low mass stars (e.g. Damjanov et al 2007;Bayo et al 2012;Riaz et al 2012;Dawson et al 2013;Downes et al 2015;Manzo-Martínez et al 2020). This results suggest that VLMS and BD could retain their primordial disks for longer times than more massive stars up to tens of Myr.…”
Section: Disk Modelmentioning
confidence: 96%